Cost for treatment and follow-up of thyroid cancer increases according to the severity of disease - Kim, Soo Young; Kim, Seok Mo; Chang, Hojin; Kim, Bup Woo; Lee, Yong Sang; Kwon, Soon Sun; Shin, Hyunjung; Chang, Hang Seok; Park, Cheong Soo (Head and Neck, 2019)
Background: The aim of this study was to provide an analysis of thyroid cancer-related health care costs over a 5-year period, according to the extent of thyroid surgery. Methods: The study included 33 patients from our institutional database who underwent thyroid cancer surgery in 2010. Patients were divided into four groups based on surgical extent: (1) hemithyroidectomy, (2) total thyroidectomy, (3) total thyroidectomy with ipsilateral radical neck dissection, and (4) total thyroidectomy with bilateral radical neck dissection and mediastinal dissection. Costs for admission and outpatient follow-up for 5 years were analyzed. Results: Costs for outpatient follow-up and admission, and overall cost increased with increasing stage of disease and increasing extent of thyroid surgery. Patients who underwent only hemithyroidectomy had the lowest costs for outpatient follow-up and admission, as well as the lowest overall cost. Conclusion: Over the 5-year follow-up period, surgery performed at an early disease stage was the most cost-effective.
Keywords: Continuity of Patient Care; Cost-Benefit Analysis; Diagnostic Imaging; Female; Follow-Up Studies; Health Care Costs; Humans; Iodine Radioisotopes; Male; Middle Aged; Neck Dissection; Patient Admission; Republic of Korea; Severity of Illness Index; Thyroid Cancer, Papillary; Thyroid Function Tests; Thyroid Neoplasms; Thyroidectomy; cost effectiveness; differentiated thyroid cancer; extent of surgery; healthcare cost; thyroid cancer